Antonio Gramsci’s “Felix Error” - Secci, Marco (International Gramsci Journal, 2025)
This paper re-examines Antonio Gramsci’s rejection of Raffaele Corso’s definition of folklore as “contemporary prehistory” and argues that the concept can be reconsidered in light of Gramsci’s critique. Gramsci opposed Corso’s positivist, evolutionary view, emphasizing instead the complexity, instability, and fragmentary nature of folklore. In the Quaderni del carcere, he framed folklore as a by-product of the dialectical relationship between hegemonic and subaltern classes, where elements of dominant culture “fall” into subaltern traditions and are recombined into contradictory worldviews. The paper suggests that folklore may indeed be understood as “contemporary prehistory,” not as a stage to be overcome, but as an unofficial, unwritten, and persistent cultural process that preserves what official history excludes. Folklore functions both conservatively, maintaining repressed social elements, and subversively, offering resources for cultural resistance. Gramsci’s background in linguistics shaped his recognition of folklore as a dynamic system akin to language—stratified, fossil-like, yet continually alive. By situating Gramsci’s contributions within broader cultural theory, the study highlights both the strength and the limits of his Marxist approach. It concludes that engaging critically with folklore remains crucial today, especially in the face of conspiracy theories and misinformation, which demonstrate its enduring social power.